2015
DOI: 10.1007/s11606-015-3512-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Conceptual Frameworks of Medical Complexity and New Model Development

Abstract: BACKGROUND: Patient complexity is often operationalized by counting multiple chronic conditions (MCC) without considering contextual factors that can affect patient risk for adverse outcomes. OBJECTIVE: Our objective was to develop a conceptual model of complexity addressing gaps identified in a review of published conceptual models. DATA SOURCES: We searched for English-language MEDLINE papers published between 1 January 2004 and 16 January 2014. Two reviewers independently evaluated abstracts and all authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 41 publications
0
74
0
2
Order By: Relevance
“…Patient-level interventions can be formulated to encourage and support patient self-management and facilitate discussions about personal preferences and priorities with HCPs, which could involve non-medical factors that may be relevant to their needs, such as the social and environmental context in which they live. 518 A 2016 Cochrane Review identified six studies of patient-level approaches to the management of multimorbidity, which included efforts such as educational support and self-management interventions. 519 The results of these six studies suggested that these interventions had little or no impact on clinical symptoms, mental health, or quality of life, indicating that patient-level interventions have limited impact when delivered in isolation.…”
Section: Patient-level Interventionsmentioning
confidence: 99%
“…Patient-level interventions can be formulated to encourage and support patient self-management and facilitate discussions about personal preferences and priorities with HCPs, which could involve non-medical factors that may be relevant to their needs, such as the social and environmental context in which they live. 518 A 2016 Cochrane Review identified six studies of patient-level approaches to the management of multimorbidity, which included efforts such as educational support and self-management interventions. 519 The results of these six studies suggested that these interventions had little or no impact on clinical symptoms, mental health, or quality of life, indicating that patient-level interventions have limited impact when delivered in isolation.…”
Section: Patient-level Interventionsmentioning
confidence: 99%
“…Heterogeneity in definition and measurement of multimorbidity is the key issue in most included systematic reviews, which led to difficulties in results comparison and precluded meta-analysis. We detected two systematic reviews focused on definition (Le Reste et al, 2013;Willadsen et al, 2016), and five focused on measurement related topics (Diederichs et al, 2011;Holzer et al, 2014;Huntley et al, 2012;Willadsen et al, 2016;Zullig et al, 2016).…”
Section: Definition and Measurementmentioning
confidence: 99%
“…Literature review about the complexity construct [8910111213] has one feature in common: the presence of other dimensions, in addition to multimorbidity, that incorporate socioeconomic determinants of health, culture, environment, patient behaviour and their experience in the use of health services that evidence social inequalities in health [1]. Grant et al suggest different complexity patterns where mental health and substance abuse were identified as the main problems in younger complex patients, while decision-making and care coordination predominated in advanced age [14].…”
Section: Introductionmentioning
confidence: 99%